First case report on molecular detection of Trypanosoma lewisi in an urban rat in Kelantan, Malaysia: An accidental finding - Kamaruzaman, Intan Noor Aina; Ting, Hong Wei; Mokhtar, Muhammad Aiman Mohd; Yuan, Yong Kai; Shah, Azim Wafiy Gulam; Hamid, Fathin Faahimaah Abdul; Zalati, Che Wan Salma Che Wan; Shaharulnizim, Nurshahirah; Reduan, Mohd Farhan Hanif; Bakar, Luqman Abu (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This case report highlights the first detection of Trypanosoma lewisi, a blood protozoan parasite found in an urban rat in Kota Bharu, Kelantan. Materials and Methods: Rat trapping was carried out within the Kota Bharu vicinity near a local wet market. A total of 38 rats were captured and subjected to peripheral blood smearing using Giemsa stain. Positive rats were sent for histopathological analysis for the evaluation of the organ samples. Results: The presence of trypanosomes was found in one sample from a blood smear. This was connected to a histological lesion on kidney tissues, which revealed a high concentration of trypanosomes. Additionally, the positive sample was confirmed as T. lewisi based on molecular diagnosis via polymerase chain reaction and subsequent sequencing and phylogenetic analysis. Conclusions: This finding serves as a baseline for further surveillance on T. lewisi population among urban rats in Kelantan and possible zoonotic transmission to humans. J. Adv. Vet. Anim. Res., 8(2): 435-439, June 2021 http://doi.org/10.5455/javar.2021.h531